Household Portfolios and Retirement Saving over the Life Cycle - Parker, Jonathan A.,Schoar, Antoinette,Cole, Allison T.,Simester, Duncan (National Bureau of Economic Research, 2022)
This paper documents the share of investable wealth that middle-class U.S. investors hold in the stock market over their working lives. This share rises modestly early in life and falls significantly as people approach retirement. Prior to 2000, the average investor held less of their investable wealth in the stock market and did not adjust this share over their working life. These changes in portfolio allocation were accelerated by the Pension Protection Act (PPA) of 2006, which allowed employers to adopt target date funds (TDFs) as default options in retirement saving plans. Young retail investors who start at an employer shortly after it adopts TDFs have higher equity shares than those who start at that same employer shortly before the change in defaults. Older investors rebalance more to safe assets. We also study retirement contribution rates over the life-cycle and find that average retirement saving rates increase steadily over the working life. In contrast to what we find for investment in the stock market, contribution rates have been stable over time and across cohorts and were not increased by the PPA
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Kapitalanlage; Anlageverhalten; Portfolio-Management; Altersvorsorge; Privater Haushalt; Mittelschicht; Lebensverlauf; USA